Eco-toxicological effects of pesticide residues on soil biological sentinels - E.I. Atuanya; T Onuoha; E Morka (Journal of Applied Sciences and Environmental Management)
This research studied the eco-toxicological effects of pesticide residues on soil biological sentinels. Nitrobacter and Nitrosomonas sp. was isolated from Soil samples gotten from dumpsite in Benin City and cultured using Winogradsky medium. The bacterial isolate was characterized and identified based on its cultural, morphological and biochemical characteristics. After 4 to 5 days of growth, Nitrobacter and Nitrosomonas Counts obtained from Winogradsky medium ranged from 1.87±0.95 to 2.43 ± 1.1 x 104cfu/g. The pesticides were observed to have negative effect on the growth of Nitrobacter and Nitrosomas sp. in broth culture media. The effective and lethal concentration (EC50) and (LC50) for each of the pesticides were observed to decrease with increase in the time of exposure and the effects of the two pesticides on both nitrite oxidations by Nitrobacter sp. and ammonia oxidation by Nitrosomonas sp. were similar. The results also showed that earthworms had weight loss and death at different concentration of the pesticide and time of exposure, with the lethal concentration (LC50) of aldrin being 2.84mg/ml while that of lindane was 3.54mg/ml after 48hr of exposure period. More so, the result obtained from this study suggest that autotrophic transformation by nitrifying bacteria and earthworm which enhances soil fertility (hence significant in crop production) may be hindered in an ecosystem polluted with these pesticide formulations, as nitrification processes will be reduced. Thus, more efforts should be geared at reducing the indiscriminate and illegal use of pesticides (banned or approved).